THEORY OF PROVOCATION AFTER MIROSLAW KARWAT - Tkachenko , Nataliya (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article is dedicated to the contemporary problem of provocation as a popular kind of manipulating, fundamentally developed by the Polish doctor of political sciences Miroslaw Karwat in his book “Theory of provocation. In Light of Political Science". This book contains the typology of the forms and methods of provocations and their functioning in communication. The linguistic, sociolinguistic and psycholinguistic methods of analysis are used. Positive provocation is constructive, determined as challenge and is applied in flirting, games, pedagogy, family conflicts, etc. Negative provocation is destructive, targeted at forcing something out of someone. The rude forms of the verbal provocation include strong emotional expressions and may be explained after M. Karwat by the intellectual helplessness or narrow mind. Provocation influence evokes illusions, hopes, changes behavior, to unusual, e. g., brutal, accumulates crisis tendencies. Positive and negative provocations are classified into active and passive, emotional and verbal, intentional and unintentional, planned and unplanned, etc. Provocation is the kind of manipulation and when positive it can develop thinking. Deceitful manipulations may be aimed at conflict, antagonism, shocking, destroying mind, triggering emotions, etc. Constructive provocation stimulates mentality, awakens thinking and conscience of society, and reveals the provocateurs’ intentions.______________ References:• Grzegorczyk, A. Życie jako wyzwanie. Wprowadzenie w filozofię racjonalistyczną (Warsaw, 1995).• Karwat, M. «Theory of Provocation. In Light of Political Science», trans. by Mikołaj Golubiewski. Studies in politics, security and society 44 (2022).• Kopaliński, Wł. Słownik wyrazow obcych i zwrotow obcojęzycznych z almanachem (Warsaw 1994).• Szulczewski, M. “Prowokacja,” in: Czas w słowach odbity (Warszawa, 1986).• Tokarski, J. (ed.), Słownik wyrazow obcych PWN (Warsaw, 1980).
Keywords: provocation, manipulation, communication, constructive, destructive